Vertical handoff research based on cognitive self-selection decision tree - Cun-qun FAN; Shang-guang WANG; Qi-bo SUN; Hua ZOU; Fang-chun YANG (Tongxin xuebao)
In heterogeneous wireless network environments, users need to access to the internet anytime, anywhere, even in a high-speed moving process. However, in the vertical handoff process, the preferences of different user and the unsta-ble network status after handoff cannot meet the switching requirement of users. So,a vertical handoff method based on cognitive self-selection decision tree was proposed. Firstly, according to the signal strength, transmission rate, bit error rate, blocking probability and movement trend, the respective handoff probability distribution of them was established and the decisions through the self-selection decision tree was made. Then, a method of feedback cognitive decision in line with the feedback of services and movements on terminals was proposed. Simulation results show that the proposed me-thod can not only ensure the vertical handoff quality of high-speed moving terminals in heterogeneous wireless networks, but also reduce unnecessary handoff and ensure the network update rate.